The hows and whys of cycling-specific testing to improve performance - Drake, S. (Performance Conditioning Cycling, 1997)
It is my objective to share some insight into the different types of testing available and what they can be used for, and to help each of you decide if and what types of testing are appropriate for you. I hope to draw on my experiences as a graduate school intern at the Sport Science and Technology Lab at the OTC as well as my work with the USA Triathlon junior and resident programs. Most recently, I spent all of 1997 as the Scouting Coach for USA Cycling, traveling back and forth across the country with the EDS/USA Cycling Scouting Program mobile exercise physiology lab conducting performance testing on junior athletes. I will start with the basics, then give a brief and simple explanation of the many different types of testing that are available and what their relative merits may be. While I understand that we are all for the most part somewhat competitive, I want to emphasize how important it is to use test data to compare yourself to yourself over time, and not to some set standard or statistic. I will be providing some of these numbers as a point of reference during the course of this article, but I want you to always keep in mind that your test results are best compared to your own previous results, and not to some set standard or to your training partner's data.